Analisis Hambatan E-Government: Sebuah Kajian Teoritis - Dian Suluh Kusuma Dewi; Dwiana Binti Yulianti; Insyira Azhar Yusdiawan (Nakhoda: Jurnal Ilmu Pemerintahan, 2022)
The existence of the Internet has a tremendous influence on human life in all fields. As a manifestation of improving services to the community, government agencies also use the Internet in providing services which are then known as e-government. E-government is designed as an internet-based service method that is able to provide fast, practical, and efficient services while providing transparency to the public. This article describes the implementation of e-government in government agencies with the aim of analyzing the obstacles found in the implementation of e-government. This article is library research where data collection is done by reviewing and exploring references in the form of articles, journals, books, magazines or other literature related to the topic under study. Data analysis was performed using Nvivo 12 plus. The results of this study indicate that there are three main obstacles in implementing e-government, namely: 1) understanding organizational culture; 2) linking political organization to the barriers of e-government, and 3) technological infrastructure barriers. Knowing these obstacles is expected to be an evaluation material for the government to better prepare for the implementation of e-government.